2019
DOI: 10.21037/atm.2019.10.84
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the relationships between tumor mutation burden with immune infiltrates in clear cell renal cell carcinoma

Abstract: Background: Whether tumor mutation burden (TMB) correlated with improved survival outcomes or promotion of immunotherapies remained controversy in various malignancies. We aimed to investigate the prognosis of TMB and the potential association with immune infiltrates in clear cell renal cell carcinoma (ccRCC). Methods:We downloaded the somatic mutation data of 336 ccRCC patients from the Cancer Genome Atlas (TCGA) database, and analyzed the mutation profiles with "maftools" package. TMB was calculated and we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 48 publications
14
90
0
Order By: Relevance
“…Previous studies have demonstrated that TILs within the TME can be regarded as a prognostic indicator in ccRCC (21). Besides, the results of GO and KEGG promoted us to continue to investigate the role of CTLA4 in TILs in ltration, which affected the ICBs' response.…”
Section: High Prognosis Value Of Ctla4 In Ccrccmentioning
confidence: 97%
“…Previous studies have demonstrated that TILs within the TME can be regarded as a prognostic indicator in ccRCC (21). Besides, the results of GO and KEGG promoted us to continue to investigate the role of CTLA4 in TILs in ltration, which affected the ICBs' response.…”
Section: High Prognosis Value Of Ctla4 In Ccrccmentioning
confidence: 97%
“…Lv et al (2020) revealed that the prognosis of bladder cancer patients with higher TMB was better so that TMB was considered to be a powerful predictor of tumor behavior and response to immunotherapy (38). However, in some types of cancer, such as clear cell renal cell carcinoma, patients with high TMB levels showed worse survival outcomes (24).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was growing evidence that higher TMB in renal cell carcinoma (RCC) was correlated with immune cell exclusion and the immunologically cold phenotypes. Accordingly, higher TMB was supposed to be associated with worse survival in RCC (24,25). These ndings stated that TMB levels may have contradictory predictions in different tumor types.…”
Section: Introductionmentioning
confidence: 95%
“…pro les and have constructed prognostic multigene signatures that can divide patients into different risk groups [15][16][17]. Previous studies have shown that IRGs were associated with the immune response intensity and predicted the prognosis of patients with PRCC [18,19].…”
Section: Recently Researchers Have Identi Ed Numerous Irgs Of Patienmentioning
confidence: 99%